İntiharın kısa tarihçesinden sebep ve yöntemlerine genel bir bakış - (:unkn) unknown (My University, 2012)
Dünyada her yıl bir milyonun üstünde kişi, tüm ölüm sebepleri içerisinde onuncu sırada yer alan intihar nedeniyle hayatlarını kaybetmektedir. Buna ek olarak her yıl 20 milyona yakın intihar girişimi meydana gelmektedir. İntihar, insanın öz benliğine yönelmiş bir saldırganlık ve yok etme eylemi olup bireyin yaşamına istemli olarak son vermesidir. Başka bir deyişle, hayatına son vermeye karar veren kişinin en etkili yöntemi seçip, kimsenin müdahalesine izin vermeyecek şekilde kendini öldürmesidir. Hala yaşıyor ise, bu bir intihar girişimidir. Çaresiz kalan kişinin sorunlarından ümitsiz bir kaçışı olarak da tanımlamaktadır. Yasalarımıza göre her intihar olayı adli bir olay olup adli tıbbi ve hukuki olarak iyi incelenmesi gereken bir durumdur. Bu yazıda, intiharın tarihçesinden, sebeplerine ve yöntemlerine kadar bilgiler derlenmiştir.

Over a million people die by suicide annually which makes it the tenth leading cause of death in the world. In addition, there are 10 to 20 million suicide attempts every year worldwide. Suicide which is an action of aggressiveness and destruction directed to human's ego is defined by the act of terminating intentionally his or her own life. In other words, suicide is the decision of the individual to end his/her life by selecting the most effective method to kill himself/herself and not allow anyone's interference. If he/she's still alive, it's called a suicide attempt. Suicide is also described as a hopeless escape of the desperate individual from his/her problems. According to our laws, every suicide case is considered as a judicial death and should be examined from the perspective of forensic medicine and laws. In this article, informations about suicide-from its history and reasons to its methods- have been reviewed
A general look at suicide, f rom its short history to its causes and used method
Keywords: Cerrahi